“FRIENDSHIP COOPERATION” WITHIN THE SISTER CITY INITIATIVE BETWEEN DAEJEON, SOUTH KOREA, AND SOUTH TANGERANG FROM 2015 TO 2019 - Hafiez, Muhammad Raihan (Yayasan Education and Social Center, 2025)
The collaboration between Daejeon and South Tangerang, according to the author's initial view, can improve the performance of the South Tangerang city government and also support the development of South Tangerang City in various aspects. The author uses descriptive qualitative research methods to analyze the cooperation that has been carried out, and uses theories and concepts such as paradiplomacy and sister city to explain the problems in the cooperation of the two cities. In this study, the authors found that the collaboration did not succeed in developing a smart city in South Tangerang. One of the reasons why the smart city collaboration between South Tangerang and Daejeon is less successful is the lack of communication. Then, the implementation of the MoU resulted in several topics of cooperation, namely social, economic, environmental, and technology. The author finds that successful collaboration is both social and technological. From the results of this study, it was found that there was a lack of communication from the South Tangerang City Government and Daejeon City Government so that the cooperation between the two cities was hampered and only resulted in some successful collaborations.